If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 20 = 3x + 6 Reorder the terms: 20 + 4x = 3x + 6 Reorder the terms: 20 + 4x = 6 + 3x Solving 20 + 4x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 20 + 4x + -3x = 6 + 3x + -3x Combine like terms: 4x + -3x = 1x 20 + 1x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 20 + 1x = 6 + 0 20 + 1x = 6 Add '-20' to each side of the equation. 20 + -20 + 1x = 6 + -20 Combine like terms: 20 + -20 = 0 0 + 1x = 6 + -20 1x = 6 + -20 Combine like terms: 6 + -20 = -14 1x = -14 Divide each side by '1'. x = -14 Simplifying x = -14
| 9s-44=2s+5 | | 48+8y=16y+16 | | 9x+6(100)=7x+700 | | (q+33)+6q=180 | | M+-5=-10 | | z+12=5z | | 92=x(x+4) | | a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 | | (4x+7)+(2x-1)=180 | | K-7=-9 | | 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 | | 2x(x-6)(3x+2)=0 | | 5a^2+3a-2=0 | | -2.3-3x-4.1-x=-3x-0.9 | | ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 |